Validation of ExPRession Learning Model-based E-Worksheet Assisted with Heyzine to Construct Computational Thinking Skill - Ficha Aulia Indah Pratiwi; Kartini Herlina; Viyanti Viyanti; Doni Andra (Jurnal Ilmiah Pendidikan Fisika, 2023)
This study aims to determine the validity of the e-worksheet based on the Expression Learning model to construct students' computational skills in direct current electric circuit material. This research was development research using Design, Development, and Research (DDR) which consisted of the analysis, design, development, and evaluation stages and used the mixed method to analyze the data. The instrument used to determine the validity of the developed e-worksheet product was an e-worksheet validation sheet. The e-worksheet validation sheet consisted of product and constructs design validity sheets which were validated by five experts who judged that the developed e-worksheet is very valid, with an average score for the construct validation test of 91.5% and an average score for design test validation of 89%. The research findings showed that ExPRession learning model-based e-worksheet assisted with Heyzine to construct computational thinking skill in direct current electric circuits material is very valid. This study provides evidence that applying the ExPRession learning model to the e-worksheet can construct students' computational thinking skills as one of the skills needed in the 21st century by teaching students the use of Microsoft Excel.